Evaluating the perception about the role of nuclear pharmacists among pharmacists in Northern Province, Sri Lanka - Praveena Priyadharshini, A.; Dhanushika Kumari, O.W.; Ranathunga, R.M.C.H.; Kalki, P.; Yoganathan, T.; Jeyanthan, M. (University of Jaffna, 2024)
Introduction: Nuclear pharmacy is a special field in pharmacy practice that requires specially trained nuclear pharmacists to handle radioactive substances. Due to ignorance, unfavourable opinions about nuclear pharmacy practice, and the role of nuclear pharmacists, fewer pharmacists are working in this field. Objective: To evaluate the perception of pharmacists about the role of Nuclear Pharmacists. Methodology: A cross-sectional descriptive study was carried out from November 2022 to November 2023 among 70 registered Pharmacists employed at government hospitals in Northern Province, Sri Lanka. A Self-administered questionnaire was used to collect data from pharmacists to assess the perception. Data was analyzed based on the research problem and objectives using Statistical Package for Social Sciences software. Results: In this study, 90.41% (n=66) of the participants responded. The majority of them were young age (72.7%), females (71.2%), married (60.6%), Sri Lankan Tamil (83.3%), and Hindus (68.2%). The majority of the participants had obtained a diploma (60.6%) whereas the remaining participants had earned a bachelor's degree. The majority had less than 10 years of working experience (45.5%), the professional position was Grade 3 (39.4%), worked in an indoor pharmacy (38.1%), participated in health-related programs (56.15%), studied related to radiopharmacy (59.1%) and have not worked as a nuclear pharmacist (92.4%). Out of the total 66 participants, 69.7% (n = 46) had a positive perception, whereas 30.3% (n = 20) had a negative perception. The findings of this study revealed that Age, gender, ethnicity, religion, marital status, educational level, years of work experience, professional position, present area of practice, participation in health-related programs, study related to nuclear pharmacy, and work experience in nuclear pharmacy were not influenced on the level of Perception (p>0.05). Conclusion: The present study revealed that the majority of the pharmacists in the Northern Province had a positive perception about the role of Nuclear Pharmacists.
Keywords: Nuclear Pharmacists; Perception; Northern province